PERANAN MADRASAH DALAM MENINGKATKAN KEMAMPUAN BAHASA ARAB SEBAGAI BAHASA INTERNASIONAL - Risvia Vahrotun Nisa’ (Institut Agama Islam Negeri (IAIN) Metro, 2018)
Madrasah is one form of Islamic educational institution that has a long history, originated from an informal education in the form of da'wah Islamiyah, then increased in the form of halaqah, until finally developed in the institution of formal education in the form of madrasah. Among one of the Islamic educational institutions that teach Arabic is Madrasah starting from Ibtida'iyah, Tsanawiyah, and Aliyah levels. In these three levels of education Arabic is presented in a classical manner with different materials tailored to their respective levels. Politically-internationally, Arabic has now been recognized as an international language and is also used as one of the official diplomatic languages ​​in the United Nations (UN) forum. Some non-Arab countries in the world, such as Malaysia, have even acknowledged Arabic in their country and give an appreciation of the existence of Arabic writing in public places. As a branch of science that stands alone, Arabic has a unique systematic and structure. Arabic learning is generally the same as other foreign language learning, which aims to achieve four kinds of skills, namely listening, speaking, reading, and writing. The skill is achieved by a learning process involving important elements such as curriculum, teaching materials, teachers, teaching methods and learning, as well as learning facilities.